Leucogaster solidus sp. nov. (Albatrellaceae, Russulales) from China - Li, Ting; Fu, Hao-Yu; Fan, Li (Phytotaxa, 2021)
Leucogaster solidus sp. nov. from southern China is described and illustrated. This species is characterized by the brown to reddish brown and verrucose basidiome, non-gelatinous gleba, thin peridium and trama, and large, globose to subglobose basidiospores with alveolate ornamentation. Phylogenetic analysis supports its taxonomic position in the genus Leucogaster.